Surface morphology and optical properties of cdse films obtained by the close-spaced vacuum sublimation technique - V.V. Starikov; M.M. Ivashchenko; A.S. Opanasyuk; V.L. Perevertaylo (Журнал нано- та електронної фізики)
Investigation of the surface morphology, growth mechanisms and optical properties of CdSe films obtained by the close-spaced vacuum sublimation (CSVS) technique, which are promising for use as the absorption layers of tandem solar cells and photodetectors, was carried out in the present paper. Measurements of the optical characteristics of the layers were performed by the spectrophotometric analysis method near the “red boundary” of semiconductor photoactivity. Performed investigations allowed to obtain the spectral distributions of the transmission T(λ), reflection R(λ), absorption α(λ), and refraction n(λ) coefficients, and the real ε1(λ) and imaginary ε2(λ) parts of the optical dielectric constant of the samples and to define their dependence on the film deposition temperature.